Hillforts of the Central Nadruvians: A Case Study of Settlement Patterns and Social Organization in Former East Prussia in the First Half of the 1st Millennium AD - Khomiakova, Olga; Skhodnov, Ivan; Chaukin, Sergey (Archaeologia Lituana, 2018)
[full article, abstract in English; abstract in Lithuanian]This article is devoted to the Central Nadruvians hillforts, located within the territory of the intercultural area of theWest Balt Circle (the so-called Inster-Pregolian group of sites), and concerns the possible role of hillforts in the context of settlement patterns and social organization in the first half of the 1st millennium AD. Morphological characteristics (sizes, structure) and the dating of Nadruvians hillforts, which can be inhabited in the Roman and Early Migration period, are discussed. Data regarding unfortified settlements and burial grounds are added. According to the results of a survey and a GIS analysis, local centers of settlement patterns in the 1st half of the first millennium AD could be formed in what can be considered a “key” for transport communications between the microregions of the Pregolya river.
Keywords: hillfort; Nadruvians; Sambian-Natangian culture; Inster-Pregolyan group of sites; cultural landscape; settlement pattern; GIS analysis